Wzajemne relacje hotelarstwa i gastronomii na rynku turystycznym - Szostak, Daniel (Mutual Relations of Hotel and Catering Industry at the Tourist Market, 2005)
Gastronomy and hotel service are the basic element of tourism infrastructure. Basic conditions of the development of contemporary tourism is creations a suitable structure of hotel and gastronomy base. There is a dependence between development of hotel and gastronomy base and development of the tourism traffic. Development of the tourism traffic leads to development of hotel trade, while existence of hotel gastronomy base contributes to intensification of the tourist traffic.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 247-252